Production-blast-induced crosscut performance in a weak biotite schist: a comparison of three high-deformation bolt types - Jones, Tristan (Luleå tekniska universitet, Geoteknologi, 2016)
In 2011, a test was installed in a crosscut on the 1022 level of the Malmberget Norra Alliansen orebody . The goal of this test was to investigate bolting support regimes and their impact on the long-term performance of the crosscut. They were installed in the most problematic geology found in the mine, weak biotite schist located primarily along the footwall contact. Three test zones included Kiruna bolts, D-bolts, and Swellex bolts, were instrumented with multi-point extensometer and strain-gaged bolts in an effort to capture the response of the bolts and the rock to both time and mine-induced stress changes. Full deformation and strain profiles in each test section indicate differences in bolt performance and stress-induced patterns occurring in the walls, shoulders and back of each bolting profile. Upprättat; 2016; 20160421 (trijon)